SEDIMENT CONTAMINANT AND TOXICITY IN KELABAT BAY, BANGKA BELITUNG PROVINCE - Hindarti, Dwi; Arifin, Zainal; Puspitasari, Rachma; Rochyatun, Endang (Marine Research in Indonesia, 2008)
Sediment of 16 sites in the Kelabat Bay were monitored for metal contamination and toxicity in 2006. Two patterns of metal contaminants distribution in the sediment were observed. Higher concentrations of lead and copper were found in March than those in July, and so was in the inner bay than those observed in the outer bay, while different pattern was observed for cadmium concentration. The highest lead concentrations were observed at site 7 (inner bay) both in March and July. Although elevated levels of cadmium, lead and copper were observed in sediments, they were still in the tolerable level for marine life. Sediment of the bay was also evaluated for its toxicity using marine phytoplankton, Chaetoceros gracilis and sea urchin, Tripneustes gratila. Results of the tests reveal that no toxic effects of sediment to the growth of phytoplankton were observed, but to sea urchin fertilization of the sediment may have toxic effect.